Apoptotic extracellular vesicles: emerging biomarkers for cancer and neurodegenerative disease diagnostics - Soleymaninejadian, Ehsan; Sadeghi Dehkordi, Marziyeh (Frontiers in Immunology, 2025)
A new subclass of extracellular vesicles formed on terminal apoptosis, apoptotic extracellular vesicles (ApoEVs), has been found to be potential markers for disease diagnosis, prognosis, and monitoring of treatment. Highlighting their role in neurological disorders and cancer as diagnostic markers, this review aims to present a new paradigm of ApoEV classification based on their biogenic process, cargo composition, and functional attributes. The heterogenous molecular content of such membrane-bound vesicles-like proteins, lipids, DNA, and RNA produces unique fingerprints reflective of the pathologic and physiological status of their parent cells. We critically examine the clinical significance, specificity, and sensitivity of current technological advancements in identifying and fractionating ApoEV through methodologies like flow cytometry, imaging processes, and molecular analysis. The prognostic and diagnostic potential of ApoEVs in cancer and neurological disease is the specific focus of this review. We address conflicting evidence, discuss controversy in the field, and contrast ApoEV-based methods with traditional biomarkers. We discuss the challenges of isolating, detecting, and validating ApoEVs and provide a standardized diagnostic procedure for clinical application. Lastly, we outline the next-generation research directions such as AI-assisted ApoEV analysis, emerging biosensor technologies, and ApoEV platforms for the specific purpose of application in personalized medicine. Finally, this thorough review critically evaluates the biological and technical hurdles which should be addressed for successful clinical translation, and the untapped potential of ApoEVs as non-invasive diagnostics.